2010
DOI: 10.1007/s12666-010-0116-8
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural characterization of dissimilar friction stir welds between AA2219 and AA5083

Abstract: Fusion welding of dissimilar aluminum alloys is very challenging. In the present work, Al-Cu alloy AA2219-T87 was friction stir welded to Al-Mg alloy AA5083-H321. Weld microstructures, hardness, and tensile properties were evaluated in as-welded condition. Microstructural studies revealed that the nugget region was primarily composed of alloy 2219, which was placed on the advancing side. No significant mixing of the two base materials in the nugget region was observed. Hardness studies revealed that the lowest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…As it's shown in the Figure, the hardness values of different aluminum side weld areas are mostly much lower than the base aluminum sheet material. The HAZ areas at the both AS and RS of the joints were found to have the minimum hardness among the other regions of the weld reportedly because of the grain coarsening or the annealing effect occurrence caused by the thermal effects on these regions [19,32]. Also the highest hardness values were achieved at the joints SZ copper sides because of the fine grain size with higher angle grain boundaries and higher density of dislocations due to the recrystallization caused by the high welding temperature and also plastic deformation from the effect of the tool pin rotational and welding speeds at these areas [2,11].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…As it's shown in the Figure, the hardness values of different aluminum side weld areas are mostly much lower than the base aluminum sheet material. The HAZ areas at the both AS and RS of the joints were found to have the minimum hardness among the other regions of the weld reportedly because of the grain coarsening or the annealing effect occurrence caused by the thermal effects on these regions [19,32]. Also the highest hardness values were achieved at the joints SZ copper sides because of the fine grain size with higher angle grain boundaries and higher density of dislocations due to the recrystallization caused by the high welding temperature and also plastic deformation from the effect of the tool pin rotational and welding speeds at these areas [2,11].…”
Section: Resultsmentioning
confidence: 92%
“…Recently many researches have been performed on similar and dissimilar FSW joints of this aluminum alloy [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Some recent researches have studied FSW of aluminium alloys in dissimilar joints [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Several different dissimilar aluminium alloy combinations have been successfully friction stir welded with reasonably good joint efficiencies [5][6][7][8][9][10][11][12]. Dilip et al [13] reported that in Friction Stir Welding of dissimilar aluminium alloys (AA5083/ AA2219), the material placed on the advancing side dominates the nugget region. Cavaliere et al [14] have studied the mechanical and microstructural properties of 2024 and 7075 aluminium alloys, which were joined together by Friction Stir Welding.…”
Section: Introductionmentioning
confidence: 99%